2022
DOI: 10.7717/peerj.13506
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical content, especially spermidine derivatives, presenting antioxidant and antilipoxygenase activities in Thai bee pollens

Abstract: Background Bee pollen (BP) is full of useful nutrients and phytochemicals.Its chemical components and bioactivities depend mainly on the type of floral pollen. Methods Monofloral BP from Camellia sinensis L., Mimosa diplotricha, Helianthus annuus L., Nelumbo nucifera, Xyris complanata, and Ageratum conyzoides were harvested. Crude extraction and partition were performed to yield solvent-partitioned extracts of each BP. Total phenolic conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Numerous studies have reported that the feeding of BP to animals resulted in a marked activation of diverse antioxidant mechanisms and an improvement in antioxidant defense against different experimentally-induced oxidative damages [ 132 , 137 , 142 , 172 , 184 , 185 ]. In addition, studies of BP extracts obtained by diverse solvents, including ethanolic [ 148 , 156 , 167 , 168 ], hydroethanolic [ 15 , 154 , 171 , 179 ], and diverse organic solvent-mediated extracts [ 150 , 151 , 153 , 175 ], have noted important antioxidant activities regardless of the extraction media. These bioeffects were also widely reported in animal models by studies that focused on different anatomical organs and physiological systems including renal [ 174 ], nervous [ 139 , 174 ], digestive [ 144 , 151 ], and reproductive [ 172 , 185 ] systems, as well as on different biochemical, hematological, and toxicological markers at systemic levels [ 137 , 165 , 184 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported that the feeding of BP to animals resulted in a marked activation of diverse antioxidant mechanisms and an improvement in antioxidant defense against different experimentally-induced oxidative damages [ 132 , 137 , 142 , 172 , 184 , 185 ]. In addition, studies of BP extracts obtained by diverse solvents, including ethanolic [ 148 , 156 , 167 , 168 ], hydroethanolic [ 15 , 154 , 171 , 179 ], and diverse organic solvent-mediated extracts [ 150 , 151 , 153 , 175 ], have noted important antioxidant activities regardless of the extraction media. These bioeffects were also widely reported in animal models by studies that focused on different anatomical organs and physiological systems including renal [ 174 ], nervous [ 139 , 174 ], digestive [ 144 , 151 ], and reproductive [ 172 , 185 ] systems, as well as on different biochemical, hematological, and toxicological markers at systemic levels [ 137 , 165 , 184 ].…”
Section: Resultsmentioning
confidence: 99%
“…For example, pollen from Eucalyptus spp. [27] and Helianthus annuus L. [28] displays a substantial inhibitory effect against tyrosinase, while pollen from Miconia spp. [27] has antihemolytic activity.…”
Section: -60%mentioning
confidence: 99%
“…[27] has antihemolytic activity. Pollen from Cocos nucifera, Miconia spp., [27] Mimosa diplotricha [28], Brassica napus [29], coriander [30], Olea europaea, and Ononis spinosa [31] has also been shown to have antioxidant activity. Furthermore, anticancer activity from Olea europaea pollen [31] and antiparasitic activity from Attalea funifera pollen [32] have been observed as a result of these compounds.…”
Section: -60%mentioning
confidence: 99%
See 1 more Smart Citation
“…Most redox energy is safely channeled in the biochemical networks, but for some unknown reason, part of the oxidizing energy flow is uncontrolled [ 2 ]. This disordered energy can, seemingly quite randomly, damage our cells, and result in oxidative-stress-related diseases such as cardiovascular disease, arthritis, cancer, atherosclerosis, aging, and neurological and neurodegenerative disorders [ 3 , 4 ]. In a healthy body, the oxidizing and reducing forces are—to a large extent—balanced and generate a reasonably controlled energy flow in which the accumulation of oxidative damage is kept within limits, and we can enjoy a lifespan of, on average, 80 years [ 5 ].…”
Section: Introductionmentioning
confidence: 99%